Certificate of completion and compliance (CCC): Towards self-certification in the Malaysian housing industry - Sufian, Azlinor (Sweet & Maxwell Asia, 2007)
For years the issue of the CFO has been debated at various levels and at various forums. Many complaints by house buyers have been heard on the delay of the issuance of the CFO or the sub-standard quality of houses despite the issuance of the CFOs. Recently the government has amended several statutes in order to facilitate the implementation of new system to replace the CFO with the CCC. The basis for removing the authority for issuance of the CFO from local authorities to professional bodies (i.e. architects and engineers) is to eradicate the problem of late issuance of the CFO which forms one of the highest number of complaints recorded by the Ministry of Housing and Local Government and the consumer associations. The CCC seems to be a move towards an international practice of building certification as practices in. the United Kingdom and New Zealand. This article seeks to discuss the requirements and processes in the issuance of the CCC and the latest amendments of related laws and by-laws namely the Housing Development (Control and Licensing) Act 1966 and the Street, Drainage and Building Act 1976.